Toward the most ideal case–control design with related and unrelated dogs in whole‐exome sequencing studies. (22nd December 2015) - Broeckx, B.J.G.; Coopman, F.; Verhoeven, G.E.C.; De Keulenaer, S.; De Meester, E.; Bavegems, V.; Smets, P.; Van Ryssen, B.; Van Nieuwerburgh, F.; Deforce, D.
Summary: With the recent development of whole‐exome sequencing enrichment designs for the dog, a novel tool for disease‐association studies became available. The aim of disease‐association studies is to identify one or a very limited number of putative causal variants or genes from the large pool of genetic variation. To maximize the efficiency of these studies and to provide some directions of what to expect, we evaluated the effect on variant reduction for various combinations of cases and controls for both dominant and recessive types of inheritance assuming variable degrees of penetrance and detectance. In this study, variant data of 14 dogs (13 Labrador Retrievers and one Dogue de Bordeaux), obtained by whole‐exome sequencing, were analyzed. In the filtering process, we found that unrelated dogs from the same breed share up to 70% of their variants, which is likely a consequence of the breeding history of the dog. For the designs tested with unrelated dogs, combining two cases and two controls gave the best result. These results were improved further by adding closely related dogs. Reduced penetrance and/or detectance has a drastic effect on the efficiency and is likely to have a profound effect on the sample size needed to elucidate the causal variant. Overall, we demonstrated that sequencing a small number of dogs results in a marked reduction of variants that are likely sufficient to pinpoint causal variants or genes.